Solving Equations and Applications Using Polynomials 4x^2-13x+3=0

4x^2 - 13x + 3 = 0; (x - 3) (4x - 1) = 0; (x - 3) = 0 or (4x - 1) = 0; x = 3 or 4x = 1; x = 1/4 The roots of 4x^2 - 13x + 3 = 0 are x = 3 or x = 1/4

s

Question

Asked 6/2/2013 7:39:54 AM

Updated 7/14/2014 11:17:59 AM

1 Answer/Comment

Edited by andrewpallarca [7/14/2014 11:16:12 AM]

Rating

3

4x^2 - 13x + 3 = 0;

(x - 3) (4x - 1) = 0;

(x - 3) = 0 or (4x - 1) = 0;

x = 3 or 4x = 1; x = 1/4

The roots of 4x^2 - 13x + 3 = 0 are x = 3 or x = 1/4

(x - 3) (4x - 1) = 0;

(x - 3) = 0 or (4x - 1) = 0;

x = 3 or 4x = 1; x = 1/4

The roots of 4x^2 - 13x + 3 = 0 are x = 3 or x = 1/4

Added 7/14/2014 11:17:59 AM

This answer has been confirmed as correct and helpful.

Dividing Polynomials 16x^2-56x+40)÷8

Question

Not Answered

Updated 6/27/2014 7:19:50 AM

1 Answer/Comment

(16x^2-56x+40)÷8 = 2x^2-7x+5

Added 6/27/2014 7:19:50 AM

This answer has been confirmed as correct and helpful.

Factor out the greatest common factor x^3+8x^2+2x+16 **Weegy:** Start with the given expression
%28x%5E3%2B8x%5E2%29%2B%282x%2B16%29 Group like terms
x%5E2%28x%2B8%29%2B2%28x%2B8%29 Factor out the GCF x%5E2 out of the first group. [ Factor out the GCF 2 out of the second group
%28x%5E2%2B2%29%28x%2B8%29 Since we have the common term x%2B8, we can combine like terms
So x%5E3%2B8x%5E2%2B2x%2B16 factors to %28x%5E2%2B2%29%28x%2B8%29
In other words, x%5E3%2B8x%5E2%2B2x%2B16=%28x%5E2%2B2%29%28x%2B8%29
] (More)

Question

Expert Answered

Updated 6/25/2014 3:27:25 AM

1 Answer/Comment

The greatest common factor of x^3+8x^2+2x+16 is 1.

Added 6/25/2014 3:27:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/1/2014 8:28:36 AM]

divide (x^3+2x^2-3x+2)÷(x+1) **Weegy:** (x^3+2x^2-3x+2)÷(x+1) = x^2+x-4 with a remainder of 6. (More)

Question

Expert Answered

Asked 6/3/2013 11:56:22 AM

0 Answers/Comments

for the polynomial function h(x)= 2x^4-x^3+2x^2-4x-3 evaluate the following h(3)

Question

Not Answered

Updated 6/9/2014 1:23:54 PM

2 Answers/Comments

h(x)= 2x^4 - x^3 + 2x^2 - 4x - 3, h(3):

h(x)= 2(3)^4 - (3)^3 + 2(3)^2 - 4(3) - 3;

h(x)= 2(81) - 27 + 2(9) - 12 - 3;

h(x)= 162 - 27 + 18 - 15;

h(x)= 135 + 3;

h(x)= 138

h(x)= 2(3)^4 - (3)^3 + 2(3)^2 - 4(3) - 3;

h(x)= 2(81) - 27 + 2(9) - 12 - 3;

h(x)= 162 - 27 + 18 - 15;

h(x)= 135 + 3;

h(x)= 138

Added 6/9/2014 1:23:54 PM

This answer has been confirmed as correct and helpful.

31,986,850

questions answered

There are no comments.